Efektivitas Model Pembelajaran Kontekstual terhadap Peningkatan Numerasi Matematika Siswa Sekolah Dasar - Riki Wahyudi; Nia Agustina; Desvia Silvana; Suci Rahmadani; Nova Umi Soimah; Angelina Maharani; Annisa Farzana Firdausi; Yeni Tavia; Fachrul Rozy; Andri Andri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Numeracy is an important skill that elementary school students must have, but in reality it is still relatively low because learning tends to be conventional and less contextual. Numeracy does not only include the ability to count, but also the ability to understand, use, and interpret numbers and data in various daily life contexts. One of the causes of low student numeracy is a learning approach that is less interesting and not related to real situations. This study aims to test the effectiveness of the contextual learning model (Contextual Teaching and Learning/CTL) in improving students' mathematical numeracy skills. The research design used was a one-group pretest-posttest experiment with 23 fifth-grade students of SDN 002 Teluk Bintan as subjects. The instrument in the form of a numeracy test was given before and after the implementation of CTL, then the data were analyzed using prerequisite tests (normality and homogeneity) followed by a paired sample t-test. The results showed a significant increase in students' numeracy skills. The average pretest score of 24.78 increased to 73.91 in the posttest with a significance value of 0.000 <0.05. This increase proves that CTL is effective in helping students master numeracy through a learning process that links mathematical concepts with real experiences. Thus, the contextual learning model can be an alternative learning strategy that is relevant for increasing elementary school students' numeracy, while emphasizing the importance of implementing a more applicable approach in mathematics learning.